2005
DOI: 10.1002/app.21806
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐beam curing of hydrogenated acrylonitrile–butadiene rubber

Abstract: ABSTRACT:The electron-beam-induced crosslinking of hydrogenated acrylonitrile-butadiene rubber (HNBR) was investigated. HNBR sheets were exposed to electron-beam irradiation in air at a room temperature of 25 Ϯ 2°C over a dose range of 0 -20 Mrad. An attempt was made to correlate the structure of the irradiated rubber with the properties. The ratio of chain scission to crosslinking and the gelation dose were determined by a method proposed elsewhere. The gel content and dynamic storage modulus increased with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…A significant reduction in the elongation at break was observed after ageing, the extent of which increased with radiation dose, and the effect of ageing was severe above 4 Mrad. This may be explained by the fact that electron beam irradiation induces oxidation and incorporates unsaturation in HNBR,8 leading to an increase in degradation of the blend during heat ageing at higher radiation doses. Nylon is also expected to produce more peroxide residues at higher radiation doses,15 which, in turn, enhances the degradation of the macromolecular chains under the influence of heat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant reduction in the elongation at break was observed after ageing, the extent of which increased with radiation dose, and the effect of ageing was severe above 4 Mrad. This may be explained by the fact that electron beam irradiation induces oxidation and incorporates unsaturation in HNBR,8 leading to an increase in degradation of the blend during heat ageing at higher radiation doses. Nylon is also expected to produce more peroxide residues at higher radiation doses,15 which, in turn, enhances the degradation of the macromolecular chains under the influence of heat.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, there is the possibility of formation of linkages between molecules of the two polymers, which could reduce the interfacial tension and provide a material with improved final properties. Electron‐beam‐radiation‐induced cross‐linking of hydrogenated nitrile rubber (HNBR) has been reported 8. Van Dyke et al 9 studied the effect of electron beam irradiation on the thermal and mechanical properties of polyamide and butyl rubber blends.…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that the insoluble content increases with increasing radiation dose, indicating that more and more HNBR molecules are crosslinked with radiation dose. In a previous article,5 we found that the gel content of HNBR increases with electron‐beam radiation dose. The insoluble content of sheets irradiated after injection molding and sample sheets made from irradiated pellets via injection molding were compared to find out whether the irradiation‐induced chemical changes of the blends are affected by sample geometry (sheet and pellet).…”
Section: Resultsmentioning
confidence: 67%
“…In such cases, there is a possibility of formation of linkages between molecules of the two polymers, which could reduce the interfacial tension and provide a material with improved ultimate properties. Electron‐beam radiation‐induced crosslinking of hydrogenated nitrile rubber (HNBR) has been discussed 5. Van Dyke et al 6 studied the effect of electron‐beam radiation on thermal and mechanical properties of polyamide and butyl rubber blends.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have applied dynamic mechanical analysis merely as a technique to characterize variously cured HNBR samples [12], a variety of HNBR and other components' blends (poly(vinyl chloride) blends [13,14,16], polycarbonate blends [15], epoxidized natural rubber blends [16], polychloroprene blends [16], poly(ethylene-vinyl acetate) blends [17], fluorocarbon elastomer blends [18]) , HNBR with different amounts of additives (iodine [19], carbon black [16,20], silica [16,20], propyl triethoxysilane [20], vinyl triethoxysilane [20], zinc diacrylate [20]), different processing conditions (vulcanization of HNBR at material/press interface and of the bulk material [21], hot air and fuel aging [22,23]) and comparison to other materials [24][25][26]; once again the dynamic mechanical properties have been reported strictly for different temperature intervals, however, not for a certain frequency range. Wrana et al [10], on the other hand, investigated the dynamic mechanical properties of vulcanized HNBR with several additives at three different frequencies, yet still within a relatively narrow frequency range (1-79 Hz) and dynamic temperature program, but no isothermal experiments were performed.…”
Section: Introductionmentioning
confidence: 99%